2022
DOI: 10.1093/eurheartjsupp/suac121.485
|View full text |Cite
|
Sign up to set email alerts
|

135 Association of Tricuspid Regurgitation With Outcome in Acute Heart Failure

Abstract: Background Tricuspid regurgitation (TR) is common in chronic heart failure (HF) and is associated with negative prognosis. However, evidence on prognostic implications of TR in acute HF (AHF) is lacking. Objectives We sought to investigate the association between TR and mortality and the interaction with pulmonary hypertension (PH) in patients admitted for AHF. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…In our population, prevalence of severe tricuspid regurgitation was 18.8%, which is higher as compared with recent studies including unselected patients with either acute or chronic heart failure, not specifically focusing on advanced heart failure. 3,4,7,8,21,22 In line with previous evidence, [6][7][8]21,22 in our study, tricuspid regurgitation severity was associated with worse clinical profile and increased heart failure severity, as patients with severe tricuspid regurgitation had a longer history of heart failure, lower blood pressure, higher NT-proBNP, worse renal function, were treated with higher doses of loop diuretics, more frequently needed inotropes/vasopressors or renal replacement therapy, and were more likely to fulfil the HFA-ESC advanced heart failure definition. Interestingly, six 'red flags' were identified as independently associated with an increased likelihood of severe tricuspid regurgitation: three clinical variables, such as history of atrial fibrillation, prior valve surgery and treatment with furosemide dose at least 120 mg/day; and three echocardiographic variables, such as LVEF at least 50%, moderate/severe mitral regurgitation and SPAP greater than 45 mmHg.…”
Section: Discussionsupporting
confidence: 89%
“…In our population, prevalence of severe tricuspid regurgitation was 18.8%, which is higher as compared with recent studies including unselected patients with either acute or chronic heart failure, not specifically focusing on advanced heart failure. 3,4,7,8,21,22 In line with previous evidence, [6][7][8]21,22 in our study, tricuspid regurgitation severity was associated with worse clinical profile and increased heart failure severity, as patients with severe tricuspid regurgitation had a longer history of heart failure, lower blood pressure, higher NT-proBNP, worse renal function, were treated with higher doses of loop diuretics, more frequently needed inotropes/vasopressors or renal replacement therapy, and were more likely to fulfil the HFA-ESC advanced heart failure definition. Interestingly, six 'red flags' were identified as independently associated with an increased likelihood of severe tricuspid regurgitation: three clinical variables, such as history of atrial fibrillation, prior valve surgery and treatment with furosemide dose at least 120 mg/day; and three echocardiographic variables, such as LVEF at least 50%, moderate/severe mitral regurgitation and SPAP greater than 45 mmHg.…”
Section: Discussionsupporting
confidence: 89%
“…had a mean age of 72 years and a mean left ventricular ejection fraction (LVEF) of 40%; 5 while the reason for echocardiography and their background pathologies and medications were not recorded, it is likely that a significant percentage had HF and left side heart disease. More recent publications consistently confirmed the association between tricuspid regurgitation and outcomes in both acute and chronic HF settings, independently of other clinical factors 6–8 . Significant tricuspid regurgitation is a frequent finding in both HF with preserved left ventricular ejection fraction (HFpEF) and HF with reduced left ventricular ejection fraction (HFrEF).…”
mentioning
confidence: 83%
“…More recent publications consistently confirmed the association between tricuspid regurgitation and outcomes in both acute and chronic HF settings, independently of other clinical factors. [6][7][8] Significant tricuspid regurgitation is a frequent finding in both HF with preserved left ventricular ejection fraction (HFpEF) and HF with reduced left ventricular ejection fraction (HFrEF). Neuhold et al 9 reported in 2013, as a surprising finding, that tricuspid regurgitation depends on the severity of chronic HF and, in more advanced HF, tricuspid regurgitation loses its additive value to predict mortality.…”
mentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Imaging , Cocianni et al 7 add to this growing body of evidence by investigating the association between TR and mortality in patients with acute HF. The authors enrolled 1176 patients with a primary diagnosis of acute HF over a 10-year period from a single institution in Italy.…”
mentioning
confidence: 99%
“…We know that waiting until the TR is severe predicts increased mortality independent of RV dysfunction, as exhibited by the present study, and others. 2,7 There is also evidence that in isolated tricuspid valve surgery, early surgery within 6 months of the diagnosis of severe TR has improved survival compared with medical therapy. 15 Timing is the key.…”
mentioning
confidence: 99%